Epidemiology of Age Related Macular Degeneration (AMD)and It?s Associated Ocular Conditions and Concomitant Systemic Diseases - Din Khan, Daulat Raheem Khan, Daulat Naghza, Naureen Karam,Fatima Amin ,Marriam Zaka,Daulat Haleem Khan Shujad (Pakistan Journal of Ophthalmology, 2018)
Purpose: To find the prevalence of AMD and its accompanying ocular or systemic diseases. Material and Methods: Epidemiological survey was conducted amongst the patients presented at different ophthalmology clinics in Lahore. Data was collected from AMD patients (n=100) through prescribed forms and was analysed for statistical significance. Results: Dry AMD (82%) was more prevalent than wet AMD (18%). Women (66%) seemed to be affected more than men (34%). In majority, AMD was found associated with other ocular conditions like cataract (78%), pseudophakia (27%), glaucoma (2%) and vitreous degeneration (3%). Interestingly, a high proportion of systemic diseases accompanied AMD like hypertension-hypercholesterolemia (72%), obesity (40%) and depression (90%). Ophthalmologists usually adopted preventive interventions against further vision loss like vitamins and minerals for dry AMD. Likewise, in wet AMD anti-VEGF, laser photocoagulation or photodynamic therapies were implied. Conclusion: AMD had a high prevalence and was often observed with other ocular conditions. Moreover, an effect of age, gender and cardiovascular diseases seemed to exist as the predisposing factors in AMD development. This study opens perspectives to conduct research to develop effective therapies for AMD.